2015
DOI: 10.15195/v2.a7
|View full text |Cite
|
Sign up to set email alerts
|

Individual Religiosity and Orientation towards Science: Reformulating Relationships

Abstract: Abstract:The religion-science relationship has been the focus of a growing body of research. Such analyses have often suffered from poorly specified concepts related to religion and to science. At the individual level, scholars often assume that an individual's religiosity will affect her orientation towards science. But an orientation towards science consists of several sub-concepts, each of which may have a unique relationship, or lack thereof, with religiosity. We use observed measures from the 2008 General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…The negative association between religiosity and science or innovation does not necessarily imply that religious people are less interested in or knowledgeable about science (Johnson et al ., ). However, confidence in science appears to be significantly lower for people that are more religious.…”
Section: Review Of Empirical Evidencementioning
confidence: 97%
“…The negative association between religiosity and science or innovation does not necessarily imply that religious people are less interested in or knowledgeable about science (Johnson et al ., ). However, confidence in science appears to be significantly lower for people that are more religious.…”
Section: Review Of Empirical Evidencementioning
confidence: 97%
“…Importantly, Evans (2013, 2018) and others (Ecklund and Scheitle 2018; Ellison and Musick 1995) have demonstrated that these debates are primarily about visions of morality and the relative social status of oneā€™s ideological group. In accordance with this, religiosity has been found to decrease confidence in institutional science but not interest in or knowledge of science (Johnson et al 2015). And in keeping with the assessment that disputes that are purportedly about science are primarily about morality and the demarcation of cultural territory, research suggests that creationist movements have long been efforts to shore up particular moral positions rather than formally challenging evolutionary theory on scientific grounds (see Alumkal 2017; Toumey 1994).…”
Section: Introductionmentioning
confidence: 81%
“…In order to address public resistance to scientific authority among the American public, we must understand the sociological dimensions of these views. Recent empirical studies have documented many of the sources of skepticism toward publicly controversial aspects of science, including the politicization of trust in science (Edgell and Hull 2017; Gauchat 2012) and religious opposition to specific issues such as evolution and the perceived moral encroachment of science (Ecklund, Peifer, et al 2017; Evans 2018; Johnson, Scheitle, and Ecklund 2015). In this study, we show that much of Americansā€™ skepticism about the authority of science and scientistsā€”skepticism that often seems motivated by fundamentalist religious beliefs and conservative politicsā€”is often premised on Christian nationalism, a religioā€political ideology that motivates a subset of American Christians to both lay claim to and contend for epistemic and moral authority in the public sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Evans (2013Evans ( , 2018 and others (Ecklund and Scheitle 2018;Ellison and Musick 1995) have demonstrated that these debates are primarily about visions of morality and the relative social status of one's ideological group. In accordance with this, religiosity has been found to decrease confidence in institutional science, but not interest in or knowledge of science (Johnson et al 2015). And in keeping with the assessment that disputes which are purportedly about science are primarily about morality and the demarcation of cultural territory, research suggests that creationist movements have long been efforts to shore up particular moral positions rather than formally challenging evolutionary theory on scientific grounds (see Alumkal 2017;Toumey 1994).…”
Section: Religion Politics and Public Opinion About Sciencementioning
confidence: 94%
“…In order to address public resistance to scientific authority among the American public, we must understand the sociological dimensions of these views. Recent empirical studies have documented many of the sources of skepticism toward publicly controversial aspects of science, including the politicization of trust in science (Guachat 2012) and religious opposition to specific issues such as evolution and the perceived moral encroachment of science (Evans 2018;Johnson et al 2015). In this study, we show that much of Americans' skepticism about the authority of science and scientists-skepticism that often seems motivated by fundamentalist religious beliefs and conservative politics-is often premised on Christian nationalism, a religio-political ideology that motivates a subset of American Christians to both lay claim to and contend for epistemic and moral authority in the public sphere.…”
Section: Introductionmentioning
confidence: 99%